Conflict and tradeoffs in decision making (Cambridge University Press, 2001)
What makes some decisions easy and others difficult? Current research in judgment and decision making indicates that conflict plays a decisive role in decision making processes. The essays in this book address questions about the causes of conflict and its effects on decision making and emotions, particularly (but not only) the emotion of regret. Several chapters address the role of attribute tradeoffs, such as that between money and risk, in the measurement of values for policy purposes. The chapters provide overviews of several current research programs and present new data. Methods involve hypothetical scenarios, other questionnaires, interviews, and observations of behavior outside the laboratory. Although most authors are influenced by psychology, others take economic and sociological approaches.